Two-Fluid Model for 1D Gas-Liquid Slug Flows: Realizable Mean Slug Characteristics. (June 2015) - Gourma, M.; Jia, N.
A two-fluid model is used to predict hydrodynamic characteristics of gas water two phase slug flows in horizontal pipes. Mathematical models are averaged based forms of balance laws with algebraic source terms. Predictions of transient solutions of such systems rely on accurate evaluations of speeds and scales of discontinuities generated by the flow conditions. Slug flows are characterized through slug frequencies, slug lengths and slug translational velocities. These are the fundamental quantities that one has to estimate in order to assess the validity of the model and the numerical method in use. A two fluid 1D model for slug flows along with an AUSMDV* numerical scheme is able to predict correct translational speeds, lengths scales and frequencies of slugs. An adaptive mesh refinement AMR procedure based on Kelvin-Helmholtz stability condition as an indicator for refinement is used to speed up simulations. The marginal Kelvin-Helmholtz stability condition is also introduced to estimate slug body length.